Post–Harvest Preservation Methods of Beans and Fear of poison among Rural Consumers in Adamawa State, Nigeria - Ogadimma ARISUKWU; Chisaa IGBOLEKWU; Festus ASAMU; ED MIBZAR (Communications of International Proceedings, 2020)
Post-harvest preservation is a fundamental aspect in agricultural production. Farmers strive to preserve their grains after harvest for so many reasons which include maximizing profit during scarcity and preserving seeds for next planting season. Although the adoption of chemical method seems effective, there has been some health risks linked to it as recorded over the years. This incidence has caused serious social apprehension to the people. Therefore, this study examines the level of perceived fear of consumption of contaminated beans among the people of Ganye. Rational choice theory was adopted for the framework. Research design for the study was exploratory and survey in nature. Data was collected using well-structured questionnaire The findings show that 61.1% of the respondents have observed a lot of post-harvest losses of beans in their area hence the common use of chemicals to preserve it. Also, 65.4% were apprehensive of consuming chemically preserved beans due to fear of food poising. This study recommends the traditional storage facility which has low or no health risk. Farmers and merchants should be enlightened through the mass media on safer ways of preserving their grains.
Keywords: Post-harvest preservation; contamination; apprehension; Beans.